Developing Posdaya for Family Empowerment - Muljono, Pudji; Agung, Sarwititi Sarwoprasojo; Bachtiar, Mintarti (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2015)
This study aims to explore the role of Posdaya in creating an ideal and harmonious of family. Poverty, changes in consumer lifestyle and weakening of the meaning of family, have the potential to encourage domestic violence and human trafficking. This study used a participatory action research approach (PAR) for the development of family-based model of empowerment throught local institutions of Posdaya. The pilot project was conducted in Posdaya Jaya Kencana, Pabean Udik Village, Indramayu District, Indramayu Regency (fishermen communities) and in Posdaya Eka Mandiri, Cihideung Udik Village, Ciampea District, Bogor Regency, West Java Province (agriculture communities). The results show that Posdaya is potential institution that can be use to develop activities to strengthen the functions of the family. In addition, Posdaya can also serve as a forum for communication in the prevention and treatment of domestic violence. Penelitian ini bertujuan untuk mengetahui peran Posdaya dalam mewujudkan keluarga yang ideal dan harmonis.  Akibat dari kemiskinan, perubahan gaya hidup konsumtif dan melemahnya makna keluarga, hal tersebut berpotensi mendorong KDRT dan human trafficking.  Penelitian ini menggunakan pendekatan participatory action research (PAR) untuk pengembangan model pemberdayaan keluarga berbasis kelembagaan lokal Posdaya. Pilot project dilakukan di Posdaya Jaya Kencana, Desa Pabean Udik, Kecamatan Indramayu, Kabupaten Indramayu (komunitas nelayan) dan di Posdaya Eka Mandiri, Desa Cihideung Udik, Kecamatan Ciampea, Kabupaten Bogor, Provinsi Jawa Barat (komunitas pertanian).  Hasil kajian menunjukkan bahwa Posdaya merupakan lembaga yang potensial dikembangkan  sebagai wadah koordinasi kegiatan penguatan fungsi-fungsi keluarga.  Selain itu, Posdaya juga dapat berfungsi sebagai forum komunikasi dalam upaya pencegahan dan penanganan KDRT.